Synergism between IL7R and CXCR4 drives BCR-ABL induced transformation in Philadelphia chromosome-positive acute lymphoblastic leukemia - Hend Abdelrasoul (Nature Portfolio, 2020)
Emergence of ABL1 kinase inhibitor resistant clones may cause disease relapse in Philadelphia chromosome-positive acute lymphoblastic leukemia. Here, the authors show interleukin 7 receptor (IL7R) signaling to contribute to this resistance mechanism, and that targeting the IL7R pathway may suppress incurable drug-resistant leukemia forms.